More aware, more protected: a cross-sectional study on road safety skills predicting the use of passive safety elements among Spanish teenagers. Issue 11 (25th November 2019) - Useche, Sergio; Alonso, Francisco; Montoro, Luis; Garrigós, Leandro
Abstract : Objective: This study had two objectives: first, to test the effects of sociodemographic variables, and the effects of three key road safety skills (knowledge–risk perception–attitudes) on the use of passive safety elements (PSEs) among teenagers; and second, to assess the differential impact of the study variables on PSEs use from a gender-based perspective. Setting and participants: This cross-sectional study was framed in the paradigm of primary care, and it involved students from several educational centres in Spain. A sample of 827 Spanish teenagers (52.4% females and 47.6% males) with a mean age of M=14.41–7 (12–19) years was used. Results: Through SEM modelling, we found that the use of PSEs is largely explained by psychosocial variables through the mediation of three road safety skills: risk perception (β=0.103 *** ), rule knowledge (β=0.095 * ) and attitudes towards road safety (β=0.186 *** ). Furthermore, multigroup analyses showed that, although most variables explain the use of PSEs among teenagers in a similar way, key gender-based differences exist in this regard. Conclusions: Road safety skills have a significant effect on the use of PSEs among Spanish teenagers, and gender explains some differences in the mechanisms which predict them. Also, in the study we discuss the need for strengthening school-based interventions aimed at helping this vulnerable group of road users acquire and develop positive behavioural competences.